Clinical Characteristics and Severity Distribution of Tertiary Eye Center Attendance by Ocular Chemical Injury Patients. Issue 7 (17th July 2022) - Akgun, Zeynep; Palamar, Melis; Egrilmez, Sait; Yagci, Ayse; Selver, Ozlem Barut
Abstract : Objectives: To report demographic characteristics, types and grades of injury, regional distribution of injury severity, clinical findings, and long-term results of acute ocular chemical burns. Methods: Medical records of patients with chemical burns between 2010 and 2020 who were admitted to Ege University less than 72 hr after the injury were reviewed. Age, gender, cause of the burn, injury severity, initial and final best-corrected visual acuity, surgical intervention, and complications were recorded. The injury severity was graded according to Dua classification. Results: A total of 104 patients (137 eyes) were included. The mean age was 42.69±17.39 (7–90) years with a male-to-female ratio of 86:18. The most common causes were home (32.6%) and industrial accidents (45.1%). The causative agent percentages for alkaline, acid, and neutral were 49.0%, 35.5%, and 5.7%, respectively. The percentages of eyes in each grade (1–6) were 16.0%, 16.0%, 15.3%, 16.7%, 17.5%, and 18.2%, respectively. Complications mostly occurred in eyes with grade 2 or higher injuries (83.7%). The relationship between injury grade and limbal stem-cell deficiency was statistically significant ( P <0.001). Surgery was mostly needed in grade 4 or higher injuries (44 eyes). Conclusion: The severity of the burn is one of the most important prognostic factors in chemical burns. It is important to determine the spreading of the regional injury severity beside the global one to predict complication risk of the injuries. In the present study, the injury distribution was homogeneous in all grades. Limbal stem-cell deficiency development took place mostly in grade 5 and 6 burns as expected.